Autopercepción de las habilidades para la cesación del tabaquismo entre los residentes de cardiología en Argentina - Sigal, Alan R. (2023)
Objective. To evaluate the self-perception of cardiology residents in Argentina regarding their abilities to help their patients stop smoking, as well as their opinions about their knowledge and skills in this area. Materials and methods. A cross-sectional study was carried out using secondary data from a study carried out in five Latin American countries and Spain, focusing on the information provided by cardiology residents in Argentina. Discrete variables were expressed as median and interquartile range, and categorical variables were expressed as percentages, and were analyzed using the chi-square test or Fisher’s exact test, depending on the relative frequency of the expected values. Results. 447 residents participated; 87.5% routinely provided brief advice to quit smoking, and 11.6% used validated questionnaires to assess the degree of addiction. Furthermore, 32.1% stated that they prescribed pharmacological treatment, but 53.1% were only familiar with a single drug. When asked about their self-perception of getting their patients to stop smoking, the median response was 5 (scale from 1 to 10); only 13.7% responded with a score of 8 or more. Conclusions. The present study suggests that cardiology residents in Argentina recognize the importance of carrying out smoking cessation interventions, but a high proportion of them do not feel qualified to do so.